(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
After gastric resection, most patients experience serious digestive disorders, a decrease in body weight [1] and the appearance of severe clinical manifestations of a number of diseases [10]. The gastrointestinal tract (GIT), as one of the subsystems of bone mineral metabolism, takes an active part in maintaining the age-related bone mass constant [4]. In diseases of the gastrointestinal tract, the absorption of minerals and vitamins (including Ca and vitamin D) is impaired. This leads to a decrease in the calcium content in bone tissue, a decrease in bone mineral density (BMD) – osteoporosis [6]. In our study, the experimental condition of osteoporosis was created by removing a certain part of the stomach by simulating the method of gastric resection by the Billroth-II method. Purpose of the study: creation of an experimental state of osteoporosis by gastric resection in experimental rats by the Billroth-II method. Study of the morphometric state of bone tissue in long tubular bones and the stomach wall. Material and methods: 27 white male rats weighing 170-200 g from the Vistar line were selected. Of these, 12 rats were divided as a control group and 15 as an experimental group. The rats of the experimental group underwent gastric resection using the Billroth-II method, and three months later morphometric changes in the long tubular bones and the stomach wall were studied. Conclusion: removal of a certain part of the stomach in experimental animals in the form of resection according to Billrot-II led to a significant morphological change in its wall, osteomorphometric parameters and architectonics of the long tubular bone..